Problem-based learning model on mathematical analytical thinking ability and science process skills - Syaiful, Syaiful; Kamid, Kamid; Kurniawan, Dwi Agus; Pratama, Wahyu Adi (Universitas Islam Raden Intan Lampung, INDONESIA, 2021)
This research serves as a reference for teachers to implement problem-based learning models on analytical thinking skills and science process skills in mathematics subjects. This research examines the differences and relationships between students' analytical thinking skills and science process skills with problem-based learning models in mathematics. The sample of this research consisted of 180 students. This research is a quantitative study with a questionnaire as the instrument. The obtained data were analyzed using the t-test and correlation test. The results showed a significant difference between analytical thinking skills and students' science process skills, especially on the indicators of Observation and Classification at SMPN 35 Batanghari and SMPN 8 Batanghari students who applied the problem-based learning model in mathematics. Furthermore, it was found that there was a relationship between analytical thinking skills and science process skills because students with analytical thinking skills possessed better science process skills in problem-based learning models in mathematics subjects.